PERAN BRAND COMMUNITY OPTIMIZATION DAN DEPENDENCE TERHADAP REPURCHASE INTENTION PADA KOMUNITAS JASA TRANSPORTASI BUS - Wisnu Sakti Dewobroto (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This research aims to figure out and analyze the effects of Brand Community Optimization, which is formed by 4 dimensions (namely: Brand Affect, Brand Trust, Brand Self-Congruity and Brand Social Identification) and Dependence towards Brand Community Commitment and Repurchase Intention. The research was done on Inter-city Inter-province (Antar Kota Antar Propinsi – AKAP) bus transportation services. The data was collected by distributing questionnaires to 300 AKAP bus community members as the samples by using the Purposive Sampling technique.. The research discovered that Brand Community Optimization is formed by 3 dimensions, which are: Brand Affect, Brand Trust and Brand Social Identification. It was found that Brand Self-Congruity is not part of the dimension that formed the Brand Community Optimization. Brand Community Optimization, in the context of the AKAP bus community, is a new variable that is proposed to take part in optimizing a certain brand to be on top of the mind of the community and create its members’ commitment to that AKAP bus brand. This study found that Brand Community Commitment acted as the Mediating Effect in the relationship between the Brand Community Optimization, Dependence with Repurchase Intention.